DEVELOPING PISA-LIKE PROBLEMS TO ASSESS STUDENTS’ MATHEMATICAL COMMUNICATION AND PROBLEM SOLVING ABILITIES - Marwanda, T.; Yusrizal, Yusrizal; Johar, Rahmah (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This research aims to produce PISA-like problems that are valid, practical, and effective for assessing students’ mathematical communication and problem solving abilities. This research type is formative evaluation development by Tessmer, including expert review, one-to-one, small group, and field test. The subject of this research is 60 students of Year 9 at SMP Negeri 19 Percontohan Banda Aceh, Indonesia. The results of this study yielded 15 PISA-like problems that are 1) valid because experts state that the set of questions developed is based on a strong theoretical basis, almost all problems have valid criteria, and the set of problems has high reliability; 2) practical because teachers agree that the problems can assess students’ mathematical communication and problem solving abilities; 3) effective because mathematical communication and problem solving abilities of students meet PISA levels and students give positive responses to PISA-like problems. The implication of this research is that mathematics teachers can use this problem to familiarize students in answering PISA-like problems, primarily to assess mathematical communication and problem solving abilities.